School composition and multiple ethnic identities of migrant-origin adolescents in the Netherlands. Issue 16 (31st December 2021) - Veerman, Gert-Jan; Platt, Lucinda
ABSTRACT: Ethnic identity is central to many contemporary discussions of belonging and assimilation of migrant-origin youth. Studies typically focus on a single minority identity. Identity theory implies, however, that individuals may hold multiple ethnic identities, or none, and these may find expression to a greater or less extent depending on context. Using a nationally representative, longitudinal study of Dutch teenagers, we investigate the role of classroom ethnic composition in shaping multiple ethnic identity expression. Framing identity choices as a relational process, we show that the number of ethnic identities that children with a migrant-origin background choose is greater for those students who are exposed to a more ethnically diverse context, while less diverse classrooms foster ethnic identification with no or fewer minority groups. Classification of migrant-origin students with a single (minority) ethnicity may thus be an oversimplification of ethnic identity, even for those from a single country of origin.